Solid Phase Extraction and Graphite furnace Atomic Absorption Spectrometry for the Determination of Palladium - Huang, Zhangjie; Chang, Jun; Feng, Shaoping; Yang, Zhongqi (Asian Journal of Chemistry, 2010)
A solid phase extraction and graphite furnace atomic absorption spectrometry (GFAAS) for the determination of palladium with Diaion SP700 resin as sorbent was studied. Palldium complexed with hexyl benzimidazolyl sulfide (HBMS) was preconcentrated on a nonpolar resin Diaion SP700 and ethanol was used as eluent. The effect of various parameters such as acidity, flow rate of sample and eluent, type of eluent, amount of adsorbent and interfering ions have been studied. The palladium in 100 mL solution can be concentrated to 1.0 mL, representing an enrichment factor of 100 was achieved. The detection limit and quantification limit of the method were found to be 0.008 and 0.2 μg L-1, respectively. The analytical results for the certified reference samples (GBW07290 and GBW07291) were in a good agreement with the certified value. The relative standard deviation for 10 replicate measurements of 0.50 μg L-1 palladium was 4.3 %. The method was successfully applied to the determination of trace amount palladium in environmental samples.